The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0004865815596794
|View full text |Cite
|
Sign up to set email alerts
|

Using environmental criminology theories to compare ‘youth misuse of fire’ across age groups in New South Wales

Abstract: Youth misuse of fire is a substantive community concern. Despite evidence which indicates youths account for a significant proportion of all deliberately lit fires within Australia, an absence of up-to-date, contextually specific research means the exact scope and magnitude of youth misuse of fire within Australia remains unknown. Despite research suggesting commonalities exist between youth misuse of fire and juvenile offending more broadly, misuse of fire is rarely explained using criminological theory. In l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…With one of the perspectives ruled out, the remaining perspective should receive more attention. It may be particularly fruitful to consider such issues from the perspective of youth, since several studies have discussed how youth often tend to be involved in fire-setting (Lowenstein, 2003;Pooley & Ferguson, 2015;Terjestam & Ryden, 1999), which also has been shown to be the case at the area-level in both the present study and previous research (Guldåker & Hallin, 2013;Malmberg et al, 2013). Large groups of youth who are experiencing strain due to unequal life chances would appear to constitute a likely explanation for arson, and future research would do well to test such a hypothesis through direct measurements of experienced strain and/or perceived inequality.…”
Section: Discussionmentioning
confidence: 99%
“…With one of the perspectives ruled out, the remaining perspective should receive more attention. It may be particularly fruitful to consider such issues from the perspective of youth, since several studies have discussed how youth often tend to be involved in fire-setting (Lowenstein, 2003;Pooley & Ferguson, 2015;Terjestam & Ryden, 1999), which also has been shown to be the case at the area-level in both the present study and previous research (Guldåker & Hallin, 2013;Malmberg et al, 2013). Large groups of youth who are experiencing strain due to unequal life chances would appear to constitute a likely explanation for arson, and future research would do well to test such a hypothesis through direct measurements of experienced strain and/or perceived inequality.…”
Section: Discussionmentioning
confidence: 99%
“…The lighting level or, conversely, the level of darkness could also be relevant. It can be seen as an indicator of the hour of the day when the crime is committed but also, lighting/darkness can play a role in facilitating crime by increasing the offenders' awareness of the space or by reducing visibility, and therefore, the capability of potential guardians (Pooley & Ferguson, 2017;Tompson & Bowers, 2013). Previous research on temperature and level of darkness in street robberies in London and Glasgow found that level of darkness was more relevant than temperature (Tompson & Bowers, 2013).…”
Section: Temporal Patterns Of Crimementioning
confidence: 99%
“…Activity spaces are made up of (a) nodes that are the places routinely visited by criminals and (b) the pathways travelled between them (Iwanski et al, 2011). Nodes may offer conditions conducive to specific crimes and thus create opportunity (Pooley and Ferguson, 2017;Rossmo, 2014). The offenders' movement from node to node therefore becomes a 'crime journey' (Bernasco, 2014).…”
Section: Thb As a Criminal Opportunitymentioning
confidence: 99%
“…regions, communities, neighbourhoods) and micro level (e.g., specific buildings or types of business) (Groff et al, 2014). At both levels, these places can be distinguished as to whether they are crime attractors or crime generators (Pooley and Ferguson, 2017). The main distinction between the two is whether offenders purposefully visit the place to commit the crime or act on impulse while there.…”
Section: Thb As a Criminal Opportunitymentioning
confidence: 99%
See 1 more Smart Citation